Anti-hyperglycemic Effect of Torbangun (Coleus amboinicus Lour) Leaves Extract Through Liver and Muscle Glycogen Deposits in Streptozotocin-induced Hyperglycmic Sprague-Dawley Rats Model - Meilla Dwi Andrestian; Rizal Damanik; Faisal Anwar; Nancy Dewi Yuliana (Medical Laboratory Technology Journal, 2019)
The association of liver and muscle glycogen deposits with serum insulin levels, β-cells pancreas, and fasting blood glucose (FBG) of streptozotocin (STZ)-induced hyperglycemic rats receiving Torbangun leaves extract (TE) investigated. The intervention performed on 25 8-week-old Sprague-Dawley rats divided into four groups. Seven rats separated as a normal group (N), and other rats injected with streptozotocin (STZ). Confirmation of hyperglycemic was characterized by fasting blood glucose >126 mg/dl. Treatment group which is NG (hyperglycemic rats); N (normal rats); H-IM (62.5 mg/kg BW metformin); and H-IT (620 mg/kg BW TE) for 14 days. This study revealed that TE significantly decreased FBG levels, increased insulin production, and the amount of liver glycogen deposits (a=0.01). However, the intervention did not significantly increase the amount of muscle glycogen deposits. TE administration improves β-cells, increases the liver and muscle glycogen deposits. TE was shown to have antihyperglycemic activity by improving the β-cell, increasing blood serum insulin levels, decreasing blood glucose levels, and increasing the liver glycogen deposits.